2018
DOI: 10.21873/anticanres.12801
|View full text |Cite
|
Sign up to set email alerts
|

The Lymph Node Ratio Is an Independent Prognostic Factor in Pancreatic Cancer Patients Who Receive Curative Resection Followed by Adjuvant Chemotherapy

Abstract: The LNR was a risk factor for overall survival in patients who underwent curative surgery followed by adjuvant chemotherapy for pancreatic cancer. It is necessary to develop strategies to effectively utilize the lymph node metastasis status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
1
19
0
3
Order By: Relevance
“…Lymph node density, or lymph node ratio, is considered a potential prognostic factor after surgery in patients with prostate, pancreatic, gastric, and esophageal malignancies. 5 - 8 Indeed, LND is more advantageous than the tumor-node-metastasis (TNM) classification system nodal staging system in predicting disease-specific survival (DSS), 9 recurrence-free survival, and overall survival (OS). 10 Likewise, in the head and neck region, LND also plays a predictive role for patients with oral cavity, thyroid, and laryngeal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node density, or lymph node ratio, is considered a potential prognostic factor after surgery in patients with prostate, pancreatic, gastric, and esophageal malignancies. 5 - 8 Indeed, LND is more advantageous than the tumor-node-metastasis (TNM) classification system nodal staging system in predicting disease-specific survival (DSS), 9 recurrence-free survival, and overall survival (OS). 10 Likewise, in the head and neck region, LND also plays a predictive role for patients with oral cavity, thyroid, and laryngeal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Hemopexin overexpression was found here to be associated with LN-metastasis number, venous invasion, lymphatic invasion, and LN ratio, which is also an accurate indicator of prognosis [36,37]. Intriguingly, tumor size did not differ between the groups, suggesting that hemopexin is more closely associated with invasion and metastasis than to tumor proliferation.…”
Section: Plos Onementioning
confidence: 48%
“…This contrasts with the results of previous research. 47 One explanation is that because patients with advanced pancreatic cancer are ineligible for surgery, fewer cases of advanced N-stage and M-stage are detected and reported. Univariate and multivariate analyses demonstrated that high CSN6 expression is a risk factor for PDAC.…”
Section: Discussionmentioning
confidence: 99%